Answer:
-The result for the radius:
[tex]6 = r[/tex]
-The result for the equation of a circle:
[tex](x-3)^2+(y-2)^2=36[/tex]
Step-by-step explanation:
The equation of a circle is:
[tex](x-h)^2+(y-k)^2=r^2[/tex] where the center is represented as [tex](h,k)[/tex], the point is known as [tex](x,y)[/tex], and the radius is represented as [tex]r[/tex] .
-Use the center (3,2) and the point (9,2) for the equation:
[tex](9-3)^2+(2-2)^2=r^2[/tex]
-Then, solve the equation to find the radius:
[tex](9-3)^2+(2-2)^2=r^2[/tex]
[tex](6)^2+0=r^2[/tex]
[tex]36 =r^2[/tex]
[tex]\sqrt{36} = \sqrt{r^2}[/tex]
[tex]6 =r[/tex]
So, the radius is 6.